The benefits of nursing care in infringement: A systematic review (Research, Society and Development, 2024)
This study examines the importance of nursing care in breastfeeding and its contributions to the health of the mother and baby. This article aims to carry out a systematic review on the benefits of nursing care in breastfeeding. The systematic review method was used, following the standards of the PRISMA declaration, to answer the guiding question mentioned in the introduction of the present study. Fourteen works published in the last five years were included. The results indicate that ongoing education and emotional support are fundamental to successful breastfeeding, suggesting the need for more robust health policies that promote evidence-based practices. The work concludes that nursing care not only facilitates the practice of breastfeeding, but also contributes significantly to maternal and child well-being.